Aripiprazole salts IV. Anionic plus solvato networks defining molecular - Freire Espeleta, Eleonora (2014)
Five new examples of aripiprazole (arip) salts are presented, viz., the Harip phthalate [Harip+·C8H5O4− (I)], homophthalate [Harip+·C9H7O4− (II)] and thiosalicilate [Harip+·C7H4O2S− (III)] salts on one side, and two different dihidrogenphosphates, Harip+·H2PO4−·2(H3PO4)·H2O (IV) and Harip+·H2PO4−·H3PO4 (V). Regarding the internal structure of the aripH+ cations, they do not differ from the already known moieties in bond distances and angles, while interesting differences in conformation can be observed, setting them apart in two groups: those in I, II and III present similar conformations to those in the so far reported arip salts presenting the same centrosymmetric R(8)22 dimeric synthon, but different to those in IV and V. In parallel, the anion (+ acid) groups define bulky systems of different dimensionality (1D in the former group, 2D in the latter). The correlation between arip molecular conformation and anionic network type is discussed. An interesting feature arises with the water solvato molecule in IV, disordered around an inversion center, in regard with its interaction with an (also disordered) phosphato O–H, in a way that an “orderly disordered” H-bonding scheme arises, complying with the S.G. symmetry requirements only on average.